Pengembangan Media Pembelajaran Power Tools Berbasis Web pada Mata Pelajaran Dasar-Dasar Teknik Otomotif (DDTO) untuk Siswa SMK - I Gusti Ngurah Made Budiana; Edi Elisa; Edy Agus Juny Artha; Kadek Rihendra Dantes; Jhony Langgeng Baruna Wirawan (MAN 4 Kota Pekanbaru, 2026)
The predominance of conventional instructional practices in vocational education frequently constrains students' conceptual understanding and independent learning, particularly in the Power Tools topic of Basic Automotive Engineering. The development and evaluation of a learning medium utilizing Google Sites constituted the primary focus of this study, with the aim of fostering instructional experiences that are both more engaging and readily accessible. Guided by the Four-D (Define, Design, Develop, and Disseminate) model within a Research and Development (R&D) framework, this study evaluated the developed learning medium through expert validation alongside practicality assessments involving vocational high school students. Feasibility assessment placed the developed learning medium in the excellent category, supported by validation scores of 98.88% from the material expert and 90.62% from the media expert. Consistent results were obtained from the practicality evaluation, which recorded 85.88% in the small-group trial and increased to 89.66% in the large-group trial. These outcomes indicate that the developed media is pedagogically sound, user-friendly, and well-suited to facilitate interactive, flexible, and learner-centered instruction in vocational education.